A “Healthy City” and a Living Place - Kapustin, Petr (project baikal, 2019)
The article considers a “healthy city” as a limited concept, which is irrelevant to the tasks of urban development. It features the conditions in the field of knowledge and ideas, where the idea of the “healthy city” can turn into another manipulation tool. The article analyses the category of “place”, which is the focus of today’s discourse, as well as suggests some proposals for the development of the given field.
Keywords: place; health; comfort; identity; city environment; manipulations and authenticity in urbanism